Pathophysiological Effects on Coronary Arteries Following Radiofrequency Ablation: A Comprehensive Review - Syed Ali Raza Abidi; Afreen Quadri; Muhammad Umer Riaz Gondal; Fatima Hayat; Shafia Naeem; Fawad Talat; Amin Mehmoodi; Jahanzeb Malik (Annals of Noninvasive Electrocardiology)
ABSTRACT Radiofrequency ablation (RFA) is a safe and effective treatment for patients experiencing ventricular and atrial tachyarrhythmias. While complications after RFA are generally rare, the occurrence of coronary artery (CA) injury, albeit infrequent, can have significant clinical implications. Given the proximity of CAs to common ablation sites, understanding the interplay between RFA and CA perfusion pathophysiology is paramount. Although previous studies have discussed the presentation and outcomes of CA injury post‐ablation, a comprehensive review consolidating the mechanisms of CA injury following RFA remains absent in the cardiology literature. In this review, we conducted an extensive literature search spanning the past three decades to explore the link between the biophysics of RFA and CA perfusion pathophysiology, focusing on injury mechanisms. We delve into RFA lesion pathology, elucidate the mechanisms of CA injury resulting from RFA, and examine factors influencing lesion formation, such as convective cooling and the “shadow effect.” Furthermore, we outline methods to mitigate CA injury post‐RFA and propose novel research avenues to optimize lesion formation and ensure the safety of arrhythmia treatments, particularly in cases where tissue ablation is performed close to CAs.